Sustainability of fish pond culture in rural farming systems of Central and Western Cameroon - T. Efole Ewoukem; O. Mikolasek; J. Aubin; M. Tomedi Eyango; V. Pouomogne; D. Ombredane (International Journal of Agricultural Sustainability, 2017)
In Sub-Saharan Africa, fish ponds are often an integral part of farming systems but have suffered from a lack of viability and sustainability. The present study aims to understand the strategies used by fish farmers to overcome economic and environmental constraints. In 2008 and 2009, fish farmers were surveyed in Central and Western Cameroon, and the fish production systems were classified by cluster analysis. Four broad types were identified according to the complexity of household operations. The development of extensive systems (large-scale and low-input) in rural areas of central Cameroon is induced mainly by abundant available land. For semi-intensive systems in both regions (small-scale and high-input in the Western Region, large-scale and high-input in peri-urban areas of the Central Region), horizontal integration is not sufficient to make fish production profitable and sustainable. More intensive fish farms tend towards vertical integration, in which farmers establish close links with input suppliers. Main causes of low productivity of semi-intensive systems (1–2 t/ha/yr) are both lack of knowledge of fish farming principles by farmers and lack of technical improvement by extension agents and researchers which need to consider the local complexity of farming systems to develop and intensify fish production. The adaptation of development strategies to socio-economic and environmental contexts is a necessity to hope for an increase in fish pond aquaculture production in Africa.